\(\left(x-1\right)^3-2\left(x-1\right)\left(x+2\right)=\left(x+2\right)^3-3\left(x-...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 6 2016

\(\left(x^3-3x^2+3x-1\right)-\left(2x^2+x-2\right)=\left(x^3+6x^2+12x+8\right)-\left(3x^2-6x+3\right)+\left(2x^2+8x+8\right)\)

\(-10x^2-24x-12=0\)

\(5x^2+12x+6=0\)

....

30 tháng 11 2016

a)\(-x^2\left(x^2-4\right)=-25\left(x^2-4\right)\)

\(\Leftrightarrow-x^2=-25\)

\(\Leftrightarrow x^2=25\)

\(\Leftrightarrow x=\pm5\)

 

 

 

 

8 tháng 7 2017

len google di ban

mk chua hoc bai nay

15 tháng 7 2017

\(\left(3x-1\right)^2+2\left(9x^2-1\right)+\left(3x+1\right)^2\)

\(=9x^2-6x+1+18x^2+2+9x^2+6x+1\)

\(=36x^2+4\)

\(\left(x^2-1\right)\left(x+3\right)-\left(x-3\right)\left(x^3+3x+9\right)\)

\(=x^3+3x^2-x+3-\left(x^4+3x^2+9x-3x^3-9x-27\right)\)

\(=x^3+3x^2-x+3-x^4-3x^2-9x+3x^3+9x-27\)

\(=\left(3x^2-3x^2\right)+\left(9x-9x\right)-x-\left(27-3\right)+x^3-x^4+3x^3\)

\(=-x-24+x^3-x^4+3x^3\)

\(\left(x+4\right)\left(x-4\right)-\left(x-4\right)^2\)

\(=x^2-16-\left(x-4\right)^2\)

\(=x^2-16-x^2+8x-16\)

\(=8x-32\)